An assessment of learning gains from educational animated videos versus traditional extension presentations among farmers in Benin*. Issue 2 (3rd April 2018) - Bello-Bravo, Julia; Tamò, Manuele; Dannon, Elie Ayitondji; Pittendrigh, Barry Robert
ABSTRACT: This study compared the efficacy of linguistically and dialectically localized animated educational videos (LAV) against traditional learning extension (TLE) presentations for learning gains of knowledge around agricultural- and healthcare-related topics within a rural population in Benin. While both approaches demonstrated learning gains, LAV resulted in significantly higher test scores and more detailed knowledge retention. A key contribution of this research, moreover, involves the use of mobile phone technologies to further disseminate educational information. That is, a majority of participants expressed both a preference for the LAV teaching approach and a heightened interest in digitally sharing the information from the educational animations with others. Because the animations are, by design, readily accessible to mobile phones via Africa's explosively expanding digital infrastructure, this heightened interest in sharing the animated videos also transforms each study participant into a potential a learning node and point of dissemination for the educational video's material as well.